“All things transregional?” in conversation with … Barbara Mittler (Trafo - Blog for transregional research, 2015)
What does Transregional Research mean? Who can learn from its insights? What are its limits? The interview series “All Things Transregional?” addresses these issues to launch an open discussion....
Gesehen am 02.11.2023